Destination Image of Goa - Jaisinghani, Deepika (2008)
Goa's tourism marketers are under pressure to diversify the tourist arrivals beyond the current heavy reliance on tourists who are looking for cheap sun-sand-sea destinations and increasing the competition in the seaside resort market from neighbouring countries such as Sri Lanka, Thailand and Malaysia. Therefore it is imperative to develop a repositioning strategy by altering certain aspects of the current image or highlighting aspects of Goa that are not included in the current image.